The Implementation of Authentic Assessment in Cultural History of Islamic Subject - Kristiawan, Muhammad; Elnanda, Depki (AT-TALIM, 2017)
This research was focused on the implementation of instructional authentic assessment in the Cutural History of Islamic Subject; class VIII, Perguruan Thawalib Putri Padang Panjang. This study aimed at describing the implementation of authentic assessment by teachers in teaching Cultural History of Islam. The design of this research was qualitative and the data collection techniques were observation and interview. The data were analysis by using Interactive Analysis Model of Miles and Huberman. The results obtained indicate that the implementation of authentic assessment had not been fully implemented by the teacher of Cultural History of Islam both in the affective and psychomotor, while the cognitive domain has been performed well.